Correlation between expression of Epidermal Growth Factor Receptor, Vascular Endothelial Growth Factor, Chemokine Receptor 4 and Vimentin by colorectal carcinoma cells - De Zoysa, M.I.M.; Samarasekera, D.N.; Senarath, L.D.J.U.; Samarasekera, C.A.; Reid, C.B. (My University, 2012)
Colorectal carcinomas are known to variably express multiple biomarkers. Increased expression of Epidermal Growth Factor Receptor (EGFR), Vascular Endothelial Growth Factor (VEGF) and Chemokine Receptor4 (CXCR4) or reduced expression of Vimentin has shown to be associated with a poor prognosis. However the correlation between expressions of these markers is hitherto not adequately evaluated.